Islam and the Environment - Ahmad Fatoni (al-Afkar, Journal For Islamic Studies, 2024)
Awareness of the importance of preserving the environment is a process that must be started together for the survival of future generations so as not to be threatened by the actions of irresponsible individuals. Various activities can be held to strengthen Islamic values and concepts related to relations between people, culture, and the environment. This study aims to examine Islamic texts contained in the Quran and Hadith. In this study, several verses of the Quran and Hadith were used, and the results of previous researchers' studies, as the main source of information using the literature review method. The results showed that environmental awareness can be strengthened in all areas of life with ecology-based Islamic teachings. Religious awareness of the preservation of the environment can be applied with a convincing approach in all situations of community life so that it has noble morals, especially the people's attitude towards the surrounding environment.